Урахування загальних засад призначення покарання у разі його призначення за вчинення кримінального правопорушення, передбаченого ст. 270 КК України - Ященко, А. М.; Yashchenko, A. M.; Ященко Андрій Миколайович (Актуальні проблеми інноваційної економіки та права. - 2024. - № 4. - С. 119-124, 2024)
У статті наголошується на тому, що на жаль, практика призначення покарання за вчинення кримінального правопорушення, передбаченого ст. 270 «Порушення встановлених законодавством вимог пожежної або техногенної безпеки» є незначною. Констатується відсутність випадків виходу суду за межі санкції при призначенні покарання за вчинення діяння, передбаченого ст. 270 КК України, що свідчить про належність формалізованої законодавцем санкції за вчинення цього правопорушення. Визначається перелік положень Загальної частини КК України, які повинні враховуватися при призначенні покарання. Констатується проблемність безпосереднього урахування ступеня тяжкості вчиненого правопорушення при призначенні покарання у контексті такого урахування відповідно до ст. 12 КК України. Зазначається, що аналіз особи винного як елементу засади призначення покарання здатний сформувати уявлення про портрет типового правопорушника, який вчиняє певне правопорушення, що в подальшому може покращити діяльність із його запобігання. У статті аналізуються основні характеристики осіб, які притягувалися до кримінальної відповідальності за вчинення діяння, передбаченого ст. 270 КК України. Окреслюється відсутність значної різноманітності щодо пом’якшуючих та обтяжуючих покарання обставин, які враховуються судом при його призначенні за вчинення діяння, передбаченого ст. 270 КК України.

The article emphasizes the importance of strict adherence to the general sentencing principles for adequately implementing the principle of legality in criminal law. The author emphasizes that, unfortunately, the practice of sentencing for a criminal offense under Article 270, "Violation of fire or industrial safety requirements established by law" of the Criminal Code of Ukraine (hereinafter - the CC of Ukraine) is almost unexplored. The analysis of the practice of sentencing for committing an act under Art. 270 of the Criminal Code of Ukraine is based on the study of more than 50 verdicts publicly available in the Unified Register of Court Decisions. The author notes that there are no cases when a court exceeded the sanction when imposing a sentence for an act under Art. 270 of the Criminal Code of Ukraine indicates that the sanction for this offense formalized by the legislator is appropriate. The author notes the almost complete absence of cases of imposing punishment for an act under Part 1 of Article 270 of the Criminal Code of Ukraine, which indicates the absolute non-prevalence of this unlawful act in Ukraine. The author determines the list of provisions of the General Part of the Criminal Code of Ukraine which should be considered when sentencing. The author notes the problematic nature of direct consideration of the degree of gravity of the offense committed when imposing punishment, especially in the context of such consideration under Article 12 of the Criminal Code of Ukraine. The author determines that the analysis of the perpetrator's personality as an element of the sentencing principle can form an idea of the portrait of a typical offender who commits a particular offense, which may further improve the activities aimed at its prevention. The article analyzes the main characteristics of persons brought to criminal liability for committing an act under Article 270 of the Criminal Code of Ukraine. The author determines that there is no significant diversity in the mitigating and aggravating circumstances that are considered by the court when imposing a sentence for an act under Article 270 of the Criminal Code of Ukraine.

Исследованы практики назначения наказания за совершение деяния, предусмотренного ст. 270 УК «Нарушение установленных законодательством требований пожарной или техногенной безопасности», выявлены определенные закономерности и осуществлены обобщения.
Account of general principles of awarding punishment in the case of his setting for the feasance of criminal offence, foreseen st., 270 Сriminal Code of Ukraine
Keywords: кримінальна відповідальність; призначення покарання; загальні засади; особа винного; порушення встановлених законодавством вимог пожежної або техногенної безпеки; пожежна безпека; техногенна безпека; диференціація кримінальної відповідальності; індивідуалізація покарання; criminal liability; sentencing; general principles; personality of the perpetrator; violation of fire or industrial safety requirements established by law; fire safety; industrial safety; differentiation of criminal liability; individualisation of punishment; уголовная ответственность; назначение наказания; общие принципы; личность виновного; нарушение установленных законодательством требований пожарной или техногенной безопасности; пожарная безопасность; техногенная безопасность; дифференциация уголовной ответственности; индивидуализация наказания